2020
DOI: 10.1126/science.aax6361
|View full text |Cite
|
Sign up to set email alerts
|

Absence of evidence for chiral Majorana modes in quantum anomalous Hall-superconductor devices

Abstract: A quantum anomalous Hall (QAH) insulator coupled to an s-wave superconductor is predicted to harbor chiral Majorana modes. A recent experiment interprets the half-quantized two-terminal conductance plateau as evidence for these modes in a millimeter-size QAH-niobium hybrid device. However, non-Majorana mechanisms can also generate similar signatures, especially in disordered samples. Here, we studied similar hybrid devices with a well-controlled and transparent interface between the superconductor and the QAH … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 45 publications
0
98
0
Order By: Relevance
“…For the (usS) case we find four expressions (for each λ E ≷ 0) for zero-energy solutions, but we need only three to define the border of the topological regions in Eq. (16). The gap is closed by an indirect closing that happens simultaneously between one band in K and one in K such that E K/K = 0.…”
Section: A Bulk Band Structure and Phase Diagramsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the (usS) case we find four expressions (for each λ E ≷ 0) for zero-energy solutions, but we need only three to define the border of the topological regions in Eq. (16). The gap is closed by an indirect closing that happens simultaneously between one band in K and one in K such that E K/K = 0.…”
Section: A Bulk Band Structure and Phase Diagramsmentioning
confidence: 99%
“…Therefore, the BdG Chern number cannot be directly connected to a quantized Hall conductance that is proportional to the number of edge states. In fact, the transport properties of samples with chiral Majorana fermions and their unique signatures are the subject of ongoing research [14][15][16].…”
Section: B Chiral Majorana Fermions In Nanoribbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, these observations came under scrutiny after replication experiments were conducted. Science published an experiment led by researchers at Pennsylvania State University in University Park contradicting the 2017 report 4 . My group reproduced patterns from the 2018 Nature study, but demonstrated that they need not originate from Majorana 5 .…”
Section: Challenging Sciencementioning
confidence: 99%
“…Based on this proposal, He et al 63 claimed to realize Majorana chiral edge states characterized by an e 2 /2h conductance plateau in Cr-doped (Bi,Sb) 2 Te 3 thin films in proximity with an Nb superconductor, but the results are questionably extrinsic. [64][65][66][67] Therefore, it is important to obtain equivalent p + ip superconductors by using intrinsic magnetic topological system. Peng and Xu 68 proposed a realization of chiral Majorana states using a heterostructure comprising MBT and an s-wave superconductor.…”
Section: Mbt-superconductor Heterostructuresmentioning
confidence: 99%